2008
DOI: 10.1063/1.3043795
|View full text |Cite
|
Sign up to set email alerts
|

Effect of transverse mode structure on the far field pattern of metal-metal terahertz quantum cascade lasers

Abstract: We elucidate the effects of the lateral mode structure on the far field pattern of metal-metal ridge-waveguide terahertz quantum cascade lasers. By introducing a 6-m-wide metal gap on the top metal contact, we suppress odd-parity lateral modes and drastically modify the far field pattern. Measurements are in good qualitative agreement with full three-dimensional finite-difference-time-domain modeling. Experimental evidence of nonuniform current pumping on the intensity distribution of the guided mode ͑and henc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…However, an accurate characterization of this effect will require integration of the output power across the entire laser far-field pattern, which is hard to quantify owing to the diffuse nature of the output beam from edge-emitting metalmetal waveguides. 15 In conclusion, we have demonstrated that the strong vertical mode confinement in metal-metal waveguides allows the reduction in the thickness of both mid-IR and THz QCL ARs far below the effective wavelength without a large increase in J th for THz devices. This result may considerably ease the demanding growth conditions for QCL ARs for which high power output is not a priority.…”
mentioning
confidence: 71%
“…However, an accurate characterization of this effect will require integration of the output power across the entire laser far-field pattern, which is hard to quantify owing to the diffuse nature of the output beam from edge-emitting metalmetal waveguides. 15 In conclusion, we have demonstrated that the strong vertical mode confinement in metal-metal waveguides allows the reduction in the thickness of both mid-IR and THz QCL ARs far below the effective wavelength without a large increase in J th for THz devices. This result may considerably ease the demanding growth conditions for QCL ARs for which high power output is not a priority.…”
mentioning
confidence: 71%
“…In contrast to the work reported in Ref. [20,21,22,23] we introduce a set-back along with additional losses given by a thin metallic layer, which is deposited onto functional devices, instead of using a highly-doped epitaxial layer. Finite element simulations are used to obtain frequency dependent optical losses in order to choose the right set-back width with respect to the laser waveguide width.…”
Section: Introductionmentioning
confidence: 99%
“…However, the consequent sub-wavelength vertical light confinement leads to highly divergent output beams from the laser facets [5]. Several strategies have been investigated to achieve more directional light output, in either edge or surface-emitting configurations, while maintaining low threshold current densities (J th ) and high T max [6][7][8].…”
mentioning
confidence: 99%